Anesthetic Considerations for an Adult Patient with Freeman-Sheldon Syndrome Undergoing Open Heart Surgery - S. Viehmeyer; P. Gabriel; K. Bauer; S. Bauer; R. Sodian; J. N. Hilberath (Case Reports in Anesthesiology)
Freeman-Sheldon syndrome (FSS) or “whistling face” syndrome is a rare congenital disorder complicated by characteristic facial deformities and muscular contractures. We report on a 64-year-old male patient presenting for surgical replacement of his aortic valve and review the available literature on anesthetic considerations and perioperative management principles. FSS frequently poses a significant challenge to airway management and gaining vascular access. Moreover, these patients are reportedly at risk for developing malignant hyperthermia (MH) or neuroleptic malignant syndrome.